ETHICAL PROBLEMS OF SALE OF MEDICINES IN PHARMACIES (British Journal of Global Ecology and Sustainable Development, 2023)
The article discusses the ethical problems of selling drugs from pharmacies. The pharmacist is the main source of information on the rational use of drugs in self-medication of the population. Professional cooperation, the concept of pharmaceutical assistance, including pharmaceutical consulting, and the code of ethics are used to overcome ethical problems in the sale of medicinal products. The unity of pharmaceutical service and pharmaceutical ethics is the basis for improving and maintaining the quality of life of patients, maintaining the health of each individual and society as a whole.